Human genome editing with CRISPR: the rebirth of eugenics? - Muhsin, Sayyed Mohamed; Chin, Alexis Heng Boon (New Media Foundation Limited, Australia, 2024)
In recent years, the emergence of CRISPR technology has ignited a fervent debate regarding its potential implications for human society, particularly in the realm of eugenics. CRISPR, with its precise gene-editing capabilities, presents both promising medical advancements and profound ethical dilemmas. The question looms: will CRISPR be used to perpetuate a new era of eugenics, whether under the guise of improving genetic health or exacerbating societal inequalities? Will it “improve or impair” society?